Plasmonic core–shell nano-heterostructures with temperature-dependent optical nonlinearity. Issue 45 (4th November 2020) - Pang, Chi; Li, Rang; Dong, Ningning; Li, Ziqi; Wang, Jun; Ren, Feng; Chen, Feng
Abstract : Plasmonics in bimetallic heterostructures have emerged as powerful tools for tunable ultrafast dynamics in nonlinear optical responses. Abstract : Plasmonics in bimetallic heterostructures have emerged as powerful tools for tunable ultrafast dynamics in nonlinear optical responses. Despite numerous studies on the mechanism of nonlinearity tailoring with various influence factors, so far, a fundamental investigation of temperature-controlled nonlinearity modulation remains blank in heterostructure systems. Here, we report on the fabrication of embedded Y@Ag/AgY core–shell nanostructures (CSNs) in fused silica for tunable nonlinearity with a laser-intensity-dependent temperature switch. Localized surface plasmon resonance (LSPR) in CSNs is substantially modified, resulting in the reconstruction of near field intensity for spatial temperature manipulation. In addition, the size effect and incident intensity dependence on the temperature of CSNs reveal improved laser tolerance with laser intensity threshold increased by 5.7 times. These results provide additional strategies for photothermal-effect-controlled nonlinearity modification in bimetallic heterostructures and unlock the potential for temperature-sensitive photonic devices under extreme conditions.